Intracervical PGE2 gel application for cervical ripening and induction of labour: a clinical study - Modi, Shilpa; Mahur, Jayalaxmi; S., Shashank V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: PGE2 gel (cerviprime) not only helps in cervical ripening but also sensitizes the uterine musculature to physiological PGE2 for generation and maintenance of uterine contractions. In the present study the efficacy of PGE2 intracerival gel for ripening and induction of labour has been reported. Methods: This is a randomized prospective study of 80 cases admitted to the labour room during period of 2 years i.e. March 2017 to March 2019 in Department of Obstetrics and Gynecology, KBNIMS, Gulbarga, Karnataka. All patients had clear indications for termination of pregnancy. The initial bishop score determined prior to induction by pelvic examination. Under aseptic precautions PGE2 endocervical gel was instilled. The results analyzed for successful ripening, induction delivery interval, results in primigravida and multigravida with single instillation or reinstallation if required, mode of delivery and maternal and perinatal complications. Results: The present study of 80 cases showed that a single application of intracervical PGE2 gel caused favorable changes in cervix by increasing Bishop score and shortened induction delivery interval with minimal side effects. Successful ripening with single application was achieved in 92.5% of cases (primi 42.5% and multi 50%). Only 6.25% of primi’s and 1.25% of multi’s required reinstallation of PGE2 gel. Successful induction was achieved in 47.5% primi’s and 50% multi’s i.e. 97.5% cases. Conclusions: The study concludes that single low dose intracervical PGE2 (cerviprime) gel proved to a safe, reliable and effective method for cervical ripening and induction of labour.